2018
DOI: 10.1093/ije/dyy201
|View full text |Cite
|
Sign up to set email alerts
|

Associations of obesity and circulating insulin and glucose with breast cancer risk: a Mendelian randomization analysis

Abstract: Background In addition to the established association between general obesity and breast cancer risk, central obesity and circulating fasting insulin and glucose have been linked to the development of this common malignancy. Findings from previous studies, however, have been inconsistent, and the nature of the associations is unclear. Methods We conducted Mendelian randomization analyses to evaluate the association of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 45 publications
10
89
1
Order By: Relevance
“…Our findings are generally in agreement with those of published umbrella reviews of the literature evidence on physical activity and adiposity with cancer risk [216][217][218], but are opposite to the results of Mendelian randomization (MR) studies. Recent publications from large-sized MR studies reported inverse associations with genetically predicted adiposity for the risk of breast cancer, overall [219] and in premenopausal [220][221][222] and postmenopausal women [220,222], which were not shown in an earlier small study [47]. One possible explanation is that genetically predicted adiposity may be more closely related to early life adiposity than later life adiposity that is largely influenced by the environment.…”
Section: Summary Of Findingsmentioning
confidence: 85%
“…Our findings are generally in agreement with those of published umbrella reviews of the literature evidence on physical activity and adiposity with cancer risk [216][217][218], but are opposite to the results of Mendelian randomization (MR) studies. Recent publications from large-sized MR studies reported inverse associations with genetically predicted adiposity for the risk of breast cancer, overall [219] and in premenopausal [220][221][222] and postmenopausal women [220,222], which were not shown in an earlier small study [47]. One possible explanation is that genetically predicted adiposity may be more closely related to early life adiposity than later life adiposity that is largely influenced by the environment.…”
Section: Summary Of Findingsmentioning
confidence: 85%
“…Multiple biological mechanisms are hypothesized to mediate the potential beneficial role of physical activity on cancer development. Greater physical activity has been associated with lower circulating levels of insulin and insulin-like growth factors, which promote cellular proliferation in breast and colorectal tissue and have also been linked to development of cancers at these sites [18][19][20][21][22][23] . Higher levels of physical activity have also been associated with lower circulating levels of estradiol, estrone, and higher levels of sex hormone binding globulin [24][25][26] which are strong risk factors for breast cancer development 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The number of IVs, variance explained, F statistic, sample size and units are described for the glycaemic exposures. The F statistic was calculated from the number of IVs, variance explained and sample size as described previously (45). The variance explained was only from the IVs utilised in this study (44).…”
Section: Selection Of Genetic Instrumental Variablesmentioning
confidence: 99%